2019
DOI: 10.1038/s41467-019-10652-9
|View full text |Cite
|
Sign up to set email alerts
|

Targeting enhancer switching overcomes non-genetic drug resistance in acute myeloid leukaemia

Abstract: Non-genetic drug resistance is increasingly recognised in various cancers. Molecular insights into this process are lacking and it is unknown whether stable non-genetic resistance can be overcome. Using single cell RNA-sequencing of paired drug naïve and resistant AML patient samples and cellular barcoding in a unique mouse model of non-genetic resistance, here we demonstrate that transcriptional plasticity drives stable epigenetic resistance. With a CRISPR-Cas9 screen we identify regulators of enhancer functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
132
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(150 citation statements)
references
References 77 publications
11
132
0
Order By: Relevance
“…Markov modeling revealed that the cell state transitions were reversible and mediated by both Lamarckian induction and nongenetic Darwinian selection of drug-tolerant states (Su et al 2017). Moreover, single-cell RNA sequencing showed that therapeutic resistance in Acute Myeloid Leukaemia (AML) emerges from a leukemia stem cell population in the form of a Lamarckian adaptive transcriptional response and, importantly, in the absence of genetic adaptation (Bell et al 2019). Note that adaptive cell state transitions are especially likely to play a major role in drug resistance in tumors with a low mutation burden.…”
Section: Implications and Opportunities For Therapymentioning
confidence: 99%
“…Markov modeling revealed that the cell state transitions were reversible and mediated by both Lamarckian induction and nongenetic Darwinian selection of drug-tolerant states (Su et al 2017). Moreover, single-cell RNA sequencing showed that therapeutic resistance in Acute Myeloid Leukaemia (AML) emerges from a leukemia stem cell population in the form of a Lamarckian adaptive transcriptional response and, importantly, in the absence of genetic adaptation (Bell et al 2019). Note that adaptive cell state transitions are especially likely to play a major role in drug resistance in tumors with a low mutation burden.…”
Section: Implications and Opportunities For Therapymentioning
confidence: 99%
“…7e). Indeed, using the published HiChIP data 43 , we detected significant reduction of long-range chromatin interactions between the MYC promoter and PVT1 enhancers after LSD1 inhibitor (LSD1i, GSK-LSD1) treatment in murine AF9 BETi-resistant AML cells (Fig. 7f).…”
Section: K562mentioning
confidence: 83%
“…In further support of its role as a TSG, heterozygous deletions of the locus or rare loss-of-function mutations of PU.1 have been described in patients with AML 9,11,54 . Moreover, oncogenic translocations or point mutations involving transcription factors such as RUNX1 abrogate the activity of PU.1 55,56 and therapeutically, the anti-leukemic activity of LSD1 inhibitors has been associated with re-activation of a PU.1 driven transcriptional programme 57,58 . However, in contrast, our study identifies Spi1/PU.1 as an oncogenic transcription factor in Npm1c/Flt3-ITD AML, and is in accord with our previous work and that of others that have demonstrated PU.1 to be a vulnerability identified by CRISPR screens in certain AML subtypes 50,51,59 .…”
Section: Discussionmentioning
confidence: 99%